Unraveling the Raman Enhancement Mechanism on 1T′‐Phase ReS2 Nanosheets. Issue 14 (7th February 2018) - Miao, Peng; Qin, Jing‐Kai; Shen, Yunfeng; Su, Huimin; Dai, Junfeng; Song, Bo; Du, Yunchen; Sun, Mengtao; Zhang, Wei; Wang, Hsing‐Lin; Xu, Cheng‐Yan; Xu, Ping
Abstract: 2D transition metal dichalcogenides materials are explored as potential surface‐enhanced Raman spectroscopy substrates. Herein, a systematic study of the Raman enhancement mechanism on distorted 1T (1T′) rhenium disulfide (ReS2 ) nanosheets is demonstrated. Combined Raman and photoluminescence studies with the introduction of an Al2 O3 dielectric layer unambiguously reveal that Raman enhancement on ReS2 materials is from a charge transfer process rather than from an energy transfer process, and Raman enhancement is inversely proportional while the photoluminescence quenching effect is proportional to the layer number (thickness) of ReS2 nanosheets. On monolayer ReS2 film, a strong resonance‐enhanced Raman scattering effect dependent on the laser excitation energy is detected, and a detection limit as low as 10 −9 m can be reached from the studied dye molecules such as rhodamine 6G and methylene blue. Such a high enhancement factor achieved through enhanced charge interaction between target molecule and substrate suggests that with careful consideration of the layer‐number‐dependent feature and excitation‐energy‐related resonance effect, ReS2 is a promising Raman enhancement platform for sensing applications. Abstract : Here the Raman enhancement mechanism on distorted 1T ReS2 nanosheets is demonstrated, where combined Raman and photoluminescence studies with the introduction of an Al2 O3 dielectric layer unambiguously reveal that Raman enhancement on ReS2 materials is from a charge transfer process rather than from an energy transfer process.